Activated Carbon Materials as Ideal Adsorbents for the Desulfurization of Fossil Fuels - Indra Neel Pulidindi; Varadarajan Thirukallam Kanthadai; Viswanathan Balasubramanian* (International Journal of Pollution: Prevention & Control, 2026)
Removal of organosulfur compounds from diesel is of interest from scientific, social, economic, and environmental viewpoints. Production of clean fuel remains a primary goal of the petroleum refining industry. The reduction of sulfur content below stringent ppm levels in diesel fuels becomesincreasingly challenging due to the presence of sterically hindered sulfur compounds, such as 4,6- dialkyldibenzothiophenes, which are resistant to removal over conventional supported mixed sulfide hydrodesulfurization catalysts. Consequently, alternative and complementary technologies based on novel approaches—including adsorption, oxidation, and chelation—are being actively explored to target these refractory sulfur species. Any significant breakthrough in desulfurization technology has the potential to positively impact human well-being by improving air quality, reducing sulfur oxide emissions, and contributing to a cleaner environment, thereby supporting efforts to mitigate climate- change-related risks. In this context, a group of activated carbon materials with high specific surface area and pronounced microporosity were systematically characterized using X-ray diffraction (XRD) for their potential application as adsorbents in the desulfurization of straight-run diesel obtained from the Cauvery Basin Refinery (CBR). In addition, the adsorption-based approach offers several advantages over conventional hydroprocessing routes, including operation under milder conditions, lower hydrogen consumption, and reduced capital and operating costs. The structural and textural properties of activated carbons—such as pore size distribution, surface heterogeneity, and crystallinity—play a crucial role in determining their affinity toward sulfur-containing aromatic compounds. Understanding the relationship between adsorbent structure and desulfurization performance is therefore essential for the rational design of efficient sorbents. The present investigation contributes to this objective by providing insights into the suitability of activated carbon materials as promising candidates for deep desulfurization of diesel fuels, particularly for the removal of refractory sulfur compounds that limit the effectiveness of conventional refining technologies.
Keywords: activated carbon; cauvery basin refinery (CBR); conventional refining technologies; desulfurization; diesel